From Intensive to Academic Listening: A Systematic Review of Listening Comprehension Strategies in Higher Education - Alfian Alfian; Meiyanti Nurchaerani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Listening comprehension is essential in higher education, particularly as students progress from basic intensive listening activities to more complex academic listening tasks. This review examines the strategies learners employ during this transition and identifies effective approaches for improving listening comprehension in University contexts. Drawing on recent research and empirical evidence, the review highlights key techniques such as metacognitive strategies, note-taking, schema activation, and contextual listening, which are crucial for academic success. The findings suggest that while intensive listening fosters foundational skills, academic listening demands advanced strategies, including critical evaluation, synthesizing information, and adapting to different accents and contexts. The review emphasizes the importance of instructional support, such as teaching explicit strategies and incorporating authentic materials, to help students navigate this shift. Educators are encouraged to create scaffolded learning experiences and foster student autonomy. This study contributes to the expanding body of knowledge on EFL and ESL education, providing useful guidance for curriculum developers and educators aiming to improve students' listening skills in higher education.